2022
DOI: 10.1111/nep.14071
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prescribing vitamin D analogues and serum vitamin D status on both contracting COVID‐19 and clinical outcomes in kidney dialysis patients'

Abstract: Aims Vitamin D plays a role in innate immune system activation, and deficiency increases susceptibility to respiratory infections and disease severity including COVID‐19. We determined whether vitamin D levels and medications were associated with contracting COVID‐19, and disease severity defined by hospitalisation and dialysis patient mortality. Methods We reviewed serum vitamin D levels, and prescription of cholecalciferol and alfacalcidol along with corresponding med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…United Kingdom (UK) approved nasal or nasopharyngeal, COVID-19 real-time reverse transcriptase-polymerase chain reaction (RT-PCR) test. 11 Patients attending for HD outpatient treatments were then routinely screened for COVID-19 whether symptomatic or not, whereas PD patients were only initially screened when symptomatic, and then as part of community contact tracing programs or when attending hospital clinics for review, and then when home testing programs were rolled out to the general public. 12 In London the predominant COVID-19 variant was the original wild type between March and July 2020, then alpha from August to December 2020, beta from January to May 2021, delta June to December 2021, and then from January 2022 omicron variants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…United Kingdom (UK) approved nasal or nasopharyngeal, COVID-19 real-time reverse transcriptase-polymerase chain reaction (RT-PCR) test. 11 Patients attending for HD outpatient treatments were then routinely screened for COVID-19 whether symptomatic or not, whereas PD patients were only initially screened when symptomatic, and then as part of community contact tracing programs or when attending hospital clinics for review, and then when home testing programs were rolled out to the general public. 12 In London the predominant COVID-19 variant was the original wild type between March and July 2020, then alpha from August to December 2020, beta from January to May 2021, delta June to December 2021, and then from January 2022 omicron variants.…”
Section: Methodsmentioning
confidence: 99%
“…Nasal and pharyngeal swabs were tested by COVID‐19 real‐time reverse transcriptase‐polymerase chain reaction (RT‐PCR), initially by the UK Public Health Service laboratory, then subsequently by a UK approved immunoassay (Roche Cobas Immunoassay platform, Roche Diagnostics Ltd, Burgess Hill, UK). United Kingdom (UK) approved nasal or nasopharyngeal, COVID‐19 real‐time reverse transcriptase‐polymerase chain reaction (RT‐PCR) test 11 . Patients attending for HD outpatient treatments were then routinely screened for COVID‐19 whether symptomatic or not, whereas PD patients were only initially screened when symptomatic, and then as part of community contact tracing programs or when attending hospital clinics for review, and then when home testing programs were rolled out to the general public 12 …”
Section: Methodsmentioning
confidence: 99%
“…A recent study reported that paricalcitol improves survival in hemodialysis patients with COVID‐19 [33]. In addition, patients with CKD, including those on dialysis who are prescribed low‐dose alfacalcidol, are at risk of contracting COVID‐19 [34].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that paricalcitol is associated with improved survival in hemodialysis patients with COVID-19 30 . In addition, patients with CKD, including those on dialysis who are prescribed low-dose alfacalcidol, are at risk of contracting COVID-19 31 .…”
Section: Discussionmentioning
confidence: 99%